PERANCANGAN SISTEM PAKAR OBAT HERBAL KONSULTASI PENYAKIT LAMBUNG MENGGUNAKAN METODE FORWARD CHAINING BERBASIS WEB - Abrar Hidayat, (2021)
Indonesia is a country that has various types of plants that can be processed into herbal medicine. However, most people do not know the benefits and properties of herbal medicines made from natural ingredients such as certain plants to treat various diseases. Therefore, this research was conducted to create an expert system that can make it easier for people to overcome diseases of the gastrointestinal system using herbal medicines. This system uses the Forward Chaining method for tracking the disease. This research is expected to help people in utilizing herbal medicine to treat gastric diseases. This system is expected to be able to revive the importance of the benefits of herbal medicine, especially in overcoming diseases of the stomach. The system is also expected to be able to make it easier and more efficient for a person to detect gastric disease early and treat it with various types of herbal medicine.